Mechanisms and substances involved in inflammation in the oral cavity – Literature review (Research, Society and Development, 2024)
Objective: The aim of the paper is to research through literature review the features of inflammation in the oral cavity and the cellular and humoral mediators involved in its development towards healing. Methodology: The searches were carried out using descriptors in PubMed Central, VHL/BIREME, Web of Science, SciELO, The Cochrane Library and Google Scholar. Furthermore, considering that this article is a narrative literature review, the vision of Rother (2007) was used to structure this work. Results: Our search resulted in 36 articles. Conclusion: The immune response in relation to the oral cavity can be considered an integrated process that involves a complex network of substances and signaling pathways to activate different cell types. The interaction between APCs, lymphocytes, NK cells and DCs, together with the regulatory effects of cytokines and chemokines, directs the final outcome of inflammatory responses in the hard and soft tissues of the oral cavity.